(untitled) (Research, Society and Development, 2021)
Objective: To test the standard protocols of a CBCT unit in order to find lower-dose alternatives with diagnostically acceptable image quality for the maxillary sinuses visualization. Study design: An observational study was performed. Two dry skulls were used to simulate four conditions of the maxillary sinuses: normality, mucous retention pseudocyst, membrane thickening and bone graft. Cone beam computed tomography scans were obtained with an i-CAT classic unit using different acquisition protocols and a box of polystyrene to simulate soft tissue attenuation. All the protocols were established by the manufacturer, combining different energy parameters, fields of view and voxel sizes. Multiplanar reconstructions were presented to three Oral Radiologists through blind and randomized distribution. The specialists judged general image quality, sharpness, contrast, and the presence of noise and artifacts based on a 4-points scale. Results: Protocols with higher energy parameters had significant association with higher scores for general quality, sharpness and contrast (p<0.05). Protocols with intermediate level of radiation dose had also significant association with good and excellent image quality; for the presence of noise and artifacts the images were rated acceptable. Conclusion: i-CAT default protocols with lower dose of radiation were able to deliver acceptable image quality for the visualization of the maxillary sinuses.